ANALISA KARAKTERISTIK AGREGAT BETON DAUR ULANG TERHADAP KUAT TEKAN BETON - Eldad Tetelepta; Mulia Pamadi (Racic : Rab Construction Research, 2026)
Occupational safety, health, and the environment (K3LH) are still often neglected by building construction workers and companies in Indonesia. This is reinforced by data on the still-high rate of workplace accidents. As a strategic industrial and trade center in the Riau Islands, Batam is experiencing rapid housing and infrastructure development. This high development intensity also increases the risk of workplace accidents. Therefore, this study aims to determine the level of understanding and implementation of K3 in the Rafflesia housing construction project. This study used a quantitative descriptive research method to analyze K3 understanding. The results of the study on the Rafflesia housing project show that theoretically, the workforce has reached a good level with an achievement of 100%. In terms of training, emergency accessibility, work areas and mobilization, and awareness of environmental and disaster risks, there are still significant differences in implementation in the field, especially in the aspect of safe behavior (rescue behavior). The majority of workers, namely 60%, still often do not use PPE, and only 70% consistently implement SOP procedures, even though the workplace accident rate remains low. To maximize the implementation of K3 in the work environment in the Rafflesia housing project, the author provides recommendations by implementing a continuous monitoring system (daily safety patrols and spot checking to ensure consistent use of PPE in the work environment.